Islamic Studies as a Comprehensive Repository of Knowledge and Wisdom: An Exploratory Analysis in the Perspective of University Students' Perceptions - Hajra,; Dr. Badshah Rehman,; Nahida Bibi, (Al Manhal Research Journal, 2024)
By the mercy and grace of ALLAH, the most compassionate, we acknowledge the divine guidance that illuminates our path. Islamic studies often perceived as a straightforward and commonplace subject holds profound significance in shaping our understanding of the world sand our place within it.by recognizing the intricate harmony between faith and science, we can bridge the gap between these seemingly disparate disciplines. Islamic studies offers a unique lens through which to explore the natural world, revealing the majesty and wisdom of ALLAH creation .by delving into its vast ocean of knowledge .we can uncover new insights, challenge assumption. Through this journey of discovery, we can reconcile faith and reason, foster personal growth and spiritual development.